The nexus of landscape: interrelation between landscape value with associated regulations in Malaysia - Teh, Mohd Zulhaili; Maulan, Suhardi; Mat Noor, Mohd Sallehuddin; Abu Bakar, Shamsul; Abdullah, Marina (Malaysian Institute Of Planners, 2024)
The landscape spectrum of Malaysia portrays rich, multiple natural and developed landscapes. Surprisingly, there are not any regulations that directly govern the landscape. It depends entirely on existing regulations that are not mentioned in detail regarding the 'landscape' specifically. As an alternative mechanism, it has several regulations used by landscape practitioners that help to manage and govern landscape planning and development. It regrets that these regulations have not been properly enforced due to some issues, which potentially can cause inefficiencies in development. Landscape value is an effective way to deeply understand the significance of landscape holistically. This study aims to examine related acts concerning landscape value in Malaysia using an archival review, identify the interrelationship of the landscape with associated regulations and analyze the relationship between these acts and the understanding of landscape in Malaysia. The findings of this research will be used to discover potentialities and constraints of the associated landscape regulations regarding their relationship with landscape value and landscape governance in Malaysia.